Implementation of Local Content Learning Media in Elementary Schools: A Study Illustration Book - Al-Pajri, Muhammad Rezki Ramdhani; Jayadi, Karta; Syahrir, Nurlina (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study intends to implement the illustrated book